To calculate \(-123.45 - (-234.76)\) using the additive inverse, we can rewrite the expression:
\[ -123.45 - (-234.76) = -123.45 + 234.76 \]
Now, we can perform the addition:
\[ 234.76 - 123.45 \]
Aligning the numbers for addition:
234.76
- 123.45
---------
Now, we perform the addition step-by-step:
-
Take the decimals into account:
- \[ 234.76 \]
- \[ -123.45 \]
- Start from the rightmost side.
-
Adding the hundredths:
- \(6 + 5 = 11\) (write 1 and carry over 1)
-
Adding the tenths:
- \(7 + 4 + 1 (carry) = 12\) (write 2 and carry over 1)
-
Adding the units:
- \(4 + 3 + 1 (carry) = 8\)
-
Adding the tens:
- \(2 + 2 = 4\)
So the addition looks like this:
234.76
- 123.45
---------
111.31
Thus, the final result is:
\[ -123.45 + 234.76 = 111.31 \]
Therefore, the answer is 111.31.